Evolution of SEMA 2002 to PERMA 2016: Mediation and its Function in Family Problem Solving - Pramudya Nawangsari, Rahma; S, Citra Widyasari (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Mediation in Indonesia is currently regulated by Supreme Court Regulation (PERMA) No. 1 of 2016 on Mediation Procedures in Court. This regulation refines earlier regulations—PERMA No. 2 of 2003 and PERMA No. 1 of 2008—by introducing updated definitions and reinforcing procedural requirements. Prior to these, the Supreme Court issued Circular Letter (SEMA) No. 1 of 2002 on Empowering First-Level Courts to Promote Peaceful Settlements. At that stage, mediation was only encouraged and not mandatory, serving as a recommended mechanism to resolve disputes amicably (dading). This study aims to examine the historical trajectory of mediation regulations in Indonesia, tracing the transition from non-binding recommendations in SEMA to the mandatory framework established through PERMA. It particularly focuses on the role and effectiveness of mediation in resolving family law cases within Religious Courts. Using a normative legal research method, this study relies on primary legal sources such as laws and Supreme Court regulations, as well as secondary sources including scholarly journals, academic books, and related literature. Findings reveal that SEMA No. 1 of 2002 marked the initial push for judges to take an active role in peaceful dispute resolution. This effort evolved into formal legal obligations with the issuance of PERMA No. 2 of 2003, its revision in PERMA No. 1 of 2008, and its refinement in PERMA No. 1 of 2016. The latter emphasized the requirement of good faith in mediation and introduced legal consequences for parties failing to comply.